Rapid and sensitive identification of ricin in environmental samples based on lactamyl agarose beads using LC‐MS/MS (MRM). (9th December 2019) - Feldberg, Liron; Schuster, Ofir; Elhanany, Eytan; Laskar, Orly; Yitzhaki, Shmuel; Gura, Sigalit
Abstract: Ricin, a plant‐derived toxin extracted from the seeds of Ricinus communis (castor bean plant), is one of the most toxic proteins known. Ricin's high toxicity, widespread availability, and ease of its extraction make it a potential agent for bioterrorist attacks. Most ricin detection methods are based on immunoassays. These methods may suffer from low efficiency in matrices containing interfering substances, or from false positive results due to antibody cross reactivity, with highly homologous proteins. In this study, we have developed a simple, rapid, sensitive, and selective mass spectrometry assay, for the identification of ricin in complex environmental samples. This assay involves three main stages: (a) Ricin affinity capture by commercial lactamyl‐agarose (LA) beads. (b) Tryptic digestion. (c) LC‐MS/MS (MRM) analysis of tryptic fragments. The assay was validated using 60 diverse environmental samples such as soil, asphalt, and vegetation, taken from various geographic regions. The assay's selectivity was established in the presence of high concentrations of competing lectin interferences. Based on our findings, we have defined strict criteria for unambiguous identification of ricin. Our novel method, which combines affinity capture beads followed by MRM‐based analysis, enabled the identification of 1 ppb ricin spiked into complex environmental matrices. This methodology has the potential to be extended for the identification of ricin in body fluids from individuals exposed (deliberately or accidentally) to the toxin, contaminated food or for the detection of the entire family of RIP‐II toxins, by applying multiplex format.